Geomagnetic effects on cosmic ray propagation under different conditions for Buenos Aires and Marambio, Argentina - Masías Meza, Jimmy Joel; Dasso, Sergio Ricardo
The geomagnetic field (Bgeo) sets a lower cutoff rigidity (Rc) to the entry of cosmic particles to Earth which depends on the geomagnetic activity. From numerical simulations of the trajectory of a proton using different models for Bgeo (performed with the MAGCOS code), we use backtracking to analyze particles arriving at the location of two nodes of the net LAGO (Large Aperture Gamma ray burst Observatory) that will be built in the near future: Buenos Aires and Marambio (Antarctica), Argentina. We determine the asymptotic trajectories and the values of Rc for different incidence directions, for each node. Simulations were done using several models for Bgeo that emulate different geomagnetic conditions. The presented results will help to make analysis of future observations of the flux of cosmic rays done at these two LAGO nodes. Fil: Masías Meza, Jimmy Joel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Física de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Física de Buenos Aires; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Física; Argentina Fil: Dasso, Sergio Ricardo. Consejo Nacional de Investigaciónes Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Astronomía y Física del Espacio. - Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Astronomía y Física del Espacio; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Física; Argentina